AB0229 Senescence associated β-galactosisdase expression in systemic sclerosis skin and fibroblasts. (23rd January 2014) - Ogawa, F.; Tomita, H.; Koike, Y.; Kuwatsuka, Y.; Utani, A.
Abstract : Background: Systemic sclerosis (SSc) is connective tissue disease characterized by fibrosis and vascular changes in the skin and internal organs with autoimmune background. However, the mechanism is still unknown. Recently, it is reported that cellular senescence is associated with fibrosis and its amelioration in several diseases. Senescence associated β-galactosidase (SA-β-gal) is one of the histological marker for the cellular senescence. Objectives: To determine association of cellar senescence in SSc skin and fibroblast. Methods: SA-β-gal expression was investigated in skin samples from SSc patients and age- and sex- matched healthy control. SA-β-gal activity was also compared in SSc patients between sclerosis lesion (forearm) and non-sclerotic lesion (upper arm). In addition, SA-β-gal expression was also investigated in fibroblasts from SSc patients and healthy control. Senescent fibroblast established by successive subculture was used for SA-β-gal staining control. Results: Senescence fibroblast showed large-scaled shape and nucleus with SA-β-gal staining. SA-β-gal expression was higher in SSc skin than control. SA-β-gal activity was observed mainly in upper dermis. Furthermore, SA-β-gal expression was observed in sclerotic skin lesion of SSc patients, however, its expression was not detected in non-sclerotic lesion of SSc patients. Furthermore, fibroblast from SSc patients showed higher SA-β-gal expression than control fibroblast. Conclusions: These results suggest that cellular senescence in SSc fibroblast may contribute to disease development in patients with SSc References: Coppe, J.P., et al., Senescence-associated secretory phenotypes reveal cell-nonautonomous functions of oncogenic RAS and the p53 tumor suppressor. PLoS Biol, 2008. 6(12): p. 2853-68. Jun, J.I. and L.F. Lau, Cellular senescence controls fibrosis in wound healing. Aging (Albany NY), 2010. 2(9): p. 627-31. Leontieva, O.V. and M.V. Blagosklonny, DNA damaging agents and p53 do not cause senescence in quiescent cells, while consecutive re-activation of mTOR is associated with conversion to senescence. Aging (Albany NY), 2010. 2(12): p. 924-35. Frippiat, C., et al., Subcytotoxic H2O2 stress triggers a release of transforming growth factor-beta 1, which induces biomarkers of cellular senescence of human diploid fibroblasts. J Biol Chem, 2001. 276(4): p. 2531-7. Disclosure of Interest: None Declared